(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
There aren’t records of Centrophoridae for the Southern Caribbean. Some of its species are generally known from bathypelagic habitats and are occasionally collected by deep exploratory field studies For the Colombian Caribbean, this is the First record of a male specimen (850 mm TL) of Centrophorus granulosus (Schneider, 1801) incidentally captured using a longline at 200 m depth on the continentalshelf off Bahía Taganga, Santa Marta.